Eco- Dystopian Narratives and the Rewriting of Hope: A Review of Environmental Consciousness in Contemporary Climate Fiction - Ibraheem, Huda Razaq (Journal of Innovation in Education and Social Research, 2025)
This review article examines how modern climate fiction transforms the meaning of dystopian narrative into an ecological and ethical context. With an emphasis on the development of the eco-dystopian narratives, it looks at the way in which authors alter the language of environmental crisis into a language of awakening, endurance and new hope. Through the theories of ecocriticism, Anthropocene theory and narrative ethics, the paper will follow the emergence and development of the environmental awareness in literature and how it influences the moral imagination of the readers. The study provides an analytical synthesis of key eco-dystopian fiction by Margaret Atwood, Kim Stanley Robinson, Richard Powers and Omar El Akkad, including MaddAddam Trilogy, The Ministry for the Future, The Overstory and American War, to demonstrate how eco-dystopian fiction strikes the right balance between the fear of apocalypticism and the hope of ecological renewal. These writings go beyond the pessimism of traditional dystopia, which offers hope not as a way to avoid the problem, but as a way to respond critically and collectively to the climate crisis. The review concludes that eco-dystopian fiction is a transformative genre that leads to environmental awareness and offers readers to affect both emotionally and ethically the vulnerability of the planet. These stories bring together realism and imaginative rejuvenation to make the dystopia a place of moral reflection and ecological engagement, and imply that even storytelling could become a form of environmental survival and a tool to rethink a sustainable future.